Teaching English as a Foreign Language Using Multiple Intelligences, Cooperative Learning and Taking into Account the Pupils’ Perceptual Learning Styles - CHEBRI, Imene (Journal of Human Sciences, 2017)
This research aims at investigating whether the implementation of cooperative learning (CL) activities, involving the insights given by Howard Gardner’s theory of multiple intelligences (MI), and taking into account the pupils’ perceptual learning styles (PLS) in secondary school EFL classrooms, will have a positive effect on pupils’ English language proficiency and attitude. An experimental study was adapted.  The place of this study was in two EFL classrooms (First year secondary school pupils, a class from the scientific stream and the other from the literary stream were taught for a whole year).  Many learning activities adapted from the first year secondary school textbook “At the Crossroads”, and  based on Gardner’s theory of Multiple Intelligences, were used while a Cooperative Learning approach was practiced, taking into account the pupils’ perceptual learning styles in designing the lesson plans.  The data for the study was collected from two sources: The first one was the pupils’ questionnaire on attitudes and motivation, regarding CL, MI, and PLS.  The second was from the pupils’ pretest and posttest scores on their language proficiency tests. The pupils’ first, mid and final-term examination marks were also taken into account.  The results of the study showed that the experimental groups that were taught using the ideas based on CL, MI, including perceptual learning styles, outperformed the control groups based on Competency Based Approach( CBA) on the stimulated English  proficiency tests for the three skills and the three achievement school examinations. Based on the results of our study, secondary school pupils can improve their achievements and their English language proficiencies through the implementation of new teaching methods based on cooperative learning, multiple intelligences theory and learners’ perceptual learning styles.